Relationship of sleep quality, chronotype, and obstructive sleep apnea with migraine in the elderly population - Fayegh, Asieh Kouhi; Mat Din, Hazwan; Wan Sulaiman, Wan Aliaa; Ravanipour, Maryam; Basri, Hamidon; Mohamed, Mohd Hazmi; Ramachandran, Vasudevan; Inche Mat, Liyana Najwa (Springer, 2023)
Purpose: Disturbances of sleep have frequently been reported in individuals with migraine. On top of this, an elderly patient with migraine also suffers from sleep disturbances due to changes in physiologic and mental health associated with aging. This study aimed to compare several sleep factors, namely sleep quality, chronotype, and obstructive sleep apnea (OSA) risk, between elderly people with and without migraine. Methods: This was a multicenter cross-sectional study conducted in 10 neurologic clinics located in Tehran, Iran, over 2 years. The sample size was calculated as 189, including 63 migraine and 126 non-migraine patients. Results: A significant difference was observed in the mean score of the global Pittsburgh Sleep Quality Index (PSQI) between migraine and non-migraine groups (p-value = 0.002), and in the individual components of the PSQI. However, there were no significant differences in the frequency of different types of chronotype (p-value = 0.125, T = 1.541) or OSA risk between the two groups (p-value = 0.568, T = –0.573). The binary logistic regression model showed that the relationship between global PSQI and migraine was significant (p= 0.002). Conclusion: Sleep quality is a problem for elderly migraine sufferers. Meanwhile, certain factors such as chronotype and OSA have no significant relationship with migraine among community-dwelling seniors. Further studies are required to enhance our understanding of this observation.